Future impacts of nitrogen deposition and climate change scenarios on forest crown defoliation. (Environmental pollution (Barking, Essex : 1987), 2014)
Defoliation is an indicator for forest health in response to several stressors including air pollutants, and one of the most important parameters monitored in the International Cooperative Programme on Assessment and Monitoring of Air Pollution Effects on Forests (ICP Forests). The study aims to estimate crown defoliation in 2030, under three climate and one nitrogen deposition scenarios, based on evaluation of the most important factors (meteorological, nitrogen deposition and chemical soil parameters) affecting defoliation of twelve European tree species. The combination of favourable climate and nitrogen fertilization in the more adaptive species induces a generalized decrease of defoliation. On the other hand, severe climate change and drought are main causes of increase in defoliation in Quercus ilex and Fagus sylvatica, especially in Mediterranean area. Our results provide information on regional distribution of future defoliation, an important knowledge for identifying policies to counteract negative impacts of climate change and air pollution.

Assessing ozone and nitrogen impact on net primary productivity with a Generalised non-Linear Model. - De Marco, Alessandra; Screpanti, Augusto; Attorre, Fabio; Proietti, Chiara; Vitale, Marcello (Environmental pollution (Barking, Essex : 1987), 2013)
Some studies suggest that in Europe the majority of forest growth increment can be accounted for N deposition and very little by elevated CO(2). High ozone (O(3)) concentrations cause reductions in carbon fixation in native plants by offsetting the effects of elevated CO(2) or N deposition. The cause-effect relationships between primary productivity (NPP) of Quercus cerris, Q. ilex and Fagus sylvatica plant species and climate and pollutants (O(3) and N deposition) in Italy have been investigated by application of Generalised Linear/non-Linear regression model (GLZ model). The GLZ model highlighted: i) cumulative O(3) concentration-based indicator (AOT40F) did not significantly affect NPP; ii) a differential action of oxidised and reduced nitrogen depositions to NPP was linked to the geographical location; iii) the species-specific variation of NPP caused by combination of pollutants and climatic variables could be a potentially important drive-factor for the plant species' shift as response to the future climate change.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 23078996
Keywords: Generalized Linear/non-Linear Model; Mediterranean climate; Net primary productivity; Nitrogen deposition; Ozone

Classifying and Mapping Potential Distribution of Forest Types Using a Finite Mixture Model - Attorre, Fabio; Francesconi, Fabio; Sanctis, Michele; Alfò, Marco; Martella, Francesca; Valenti, Roberto; Vitale, Marcello (Folia Geobotanica, 2012)
The present paper presents the application of a finite mixture model (FMM) to analyze spatially explicit data on forest composition and environmental variables to produce a high-resolution map of their current potential distribution. FMM provides a convenient yet formal setting for model-based clustering. Within this framework, forest data are assumed to come from an underlying FMM, where each mixture component corresponds to a cluster and each cluster is characterized by a different composition of tree species. An important extension of this model is based on including a set of covariates to predict class membership. These covariates can be climatic and topographical parameters as well as geographical coordinates and the class membership of neighbouring plots. FMM was applied to a national forest inventory of Italy consisting of 6,714 plots with a measure of abundance for 27 tree species. In this way, a map of potential forest types was produced. The limitations and usefulness of the proposed modelling approach were analyzed and discussed, comparing the results with an independently derived expert map
Keywords: Classification; Finite Mixture Model; forest types; Italy; Potential distribution

Is cellular automata algorithm able to predict the future dynamical shifts of tree species in Italy under climate change scenarios? A methodological approach - Di Traglia, Mario; Attorre, Fabio; Francesconi, Fabio; Valenti, Roberto; Vitale, Marcello (Ecological Modelling, 2011)
In this paper is presented a methodological approach which integrates statistic modelling and 2-D cellular automata (CA) in order to describe tree species shifts responding to the climate changes foreseen for Italy in the 21st century. Five Italian tree species populations of Abies alba, Pinus sylvestris, Fagus sylvatica, Acer campestris and Quercus suber and their actual potential distributions (PDs) – represented by Importance Value (IV), have been considered. Environmental and climatic relationships have been modelled through application of a new statistical methodology called extreme discretization, where the PD of a species was considered as a random ﬁeld. The IV-based PD has been spatialized through a probability function (A,S), which represented the spatio-temporal relationships between IV values and climatic (A) and geomorphological (S) variables. For each tree species = (A,S) has been estimated and inserted as rule in the 2-D cellular automata. The latter, acting by a Moore neighbouring, took in consideration also the suitability map for tree species, which has been obtained by land cover map. Two time frames (2050 and 2080) and two climatic scenarios (A2 and B1) have been considered. Results described a general reduction of the IV values and their distribution for A. alba, P. sylvestris and F. sylvatica, in both climatic scenarios, whereas an increase of IVs and distribution for Q. suber and only a slight increment of distribution for A. campestris was mainly observed under the B1 scenario, but not for the more limiting A2 scenario. Convergent results have been obtained with respect to other simulation systems concerning the shift of tree species responding to different climatic change scenarios but lacking of the description of dynamical paths. Our approach seems natural and practical to describe such phenomena. The transition rules for the CA and the parameters taken into account for the construction of the probabilistic models can be surely improved to obtain a more realistic pattern of tree species shifts. Future efforts should be made to take in account the inter-speciﬁc relationships inside the Italian forest ecosystems, in order to also consider the competiveness for resources that exert some effects on the plant distribution both in time and space.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: 2-d cellular automata; climate change; Importance Value; Logistic analysis; Mediterranean basin; Potential tree species shift

Evaluating the effects of climate change on tree species abundance and distribution in the Italian peninsula - Attorre, Fabio; Alfò, Marco; De Sanctis, Michele; Francesconi, Fabio; Valenti, Roberto; Vitale, Marcello; Bruno, Franco (Applied Vegetation Science, 2011)
Question: What is the effect of climate change on tree species abundance and distribution in the Italian peninsula? Location: Italian peninsula. Methods: Regression tree analysis, Random Forest, generalized additive model and geostatistical methods were compared to identify the best model for quantifying the effect of climate change on tree species distribution and abundance. Future potential species distribution, richness, local colonization, local extinction and species turnover were modelled according to two scenarios (A2 and B1) for 2050 and 2080. Results: Robust Random Forest proved to be the best statistical model to predict the potential distribution of tree species abundance. Climate change could lead to a shift in tree species distribution towards higher altitudes and a reduction of forest cover. Pinus sylvestris and Tilia cordata may be considered at risk of local extinction, while the other species could ﬁnd potential suitable areas at the cost of a rearrangement of forest community composition and increasing competition. Conclusions: Geographical and topographical regional characteristics can have a noticeable inﬂuence on the impact of predicted climate change on forest ecosystems within the Mediterranean basin. It would be highly beneﬁcial to create a standardized and harmonized European forest inventory in order to evaluate, at high resolution, the effect of climate change on forest ecosystems, identify regional differences and develop speciﬁc adaptive management strategies and plans.
Keywords: generalized additive model; geostatistical; geostatistical methods; italian peninsula; methods; random forest; regression tree analysis

Physiological responses of Quercus ilex Leaves to Water Stress and Acute Ozone Exposure Under Controlled Conditions - Vitale, Marcello; Salvatori, Elisabetta; Loreto, Francesco; Fares, Silvano; Manes, Fausto (Water, Air, and Soil Pollution, 2007)
The combined effect of water stress and ozone (O3) on stomatal O3 flux, damage to photosynthesis, and detoxification by biogenic volatile organic compounds (BVOC) in Quercus ilex leaves was studied. A 4-weeks O3 exposure (250 ppb, 4 h per day) caused a reduction of photosynthesis and stomatal conductance, which was fully recovered 1 week after the end of the treatment, in well-watered and water-stressed plants. Measurements of stomatal O3 flux revealed a low stomatal flux of the pollutant, which became minimal after stomatal closure caused by water stress. An induction of volatile monoterpenes, important compounds in the O3 scavenging system in Q. ilex, and a burst of lipoxygenase compounds (LOX), which are released as gaseous by-products of membrane peroxidation, was observed after 2–3 weeks of O3 fumigation. However, these compounds were also released in control leaves that were exposed to ozone only briefly, to determine stomatal O3 flux. The low stomatal flux that occurred in water stress conditions helped avoiding permanent damage to Q. ilex leaves, although during the O3 treatment photosynthesis was severely limited by stomatal closure. In well-watered plants, O3 fumigation caused a noticeable increase of nocturnal stomatal conductance. If confirmed on adult plants under field conditions, this effect can imply larger flux of O3 at night and possible detrimental effects of O3 on leaf functions in plants exposed to high nocturnal O3 levels.
Keywords: Gas exchange; Holm oak (Quercus ilex); lipoxygenase products; monoterpene emission; o3 flux; photosynthesis; Stomatal conductance

Physiological responses of Quercus ilex Leaves to Water Stress and Acute Ozone Exposure Under Controlled Conditions (Water, Air, and Soil Pollution, 2007)
The combined effect of water stress and ozone (O3) on stomatal O3 flux, damage to photosynthesis, and detoxification by biogenic volatile organic compounds (BVOC) in Quercus ilex leaves was studied. A 4-weeks O3 exposure (250 ppb, 4 h per day) caused a reduction of photosynthesis and stomatal conductance, which was fully recovered 1 week after the end of the treatment, in well-watered and water-stressed plants. Measurements of stomatal O3 flux revealed a low stomatal flux of the pollutant, which became minimal after stomatal closure caused by water stress. An induction of volatile monoterpenes, important compounds in the O3 scavenging system in Q. ilex, and a burst of lipoxygenase compounds (LOX), which are released as gaseous by-products of membrane peroxidation, was observed after 2–3 weeks of O3 fumigation. However, these compounds were also released in control leaves that were exposed to ozone only briefly, to determine stomatal O3 flux. The low stomatal flux that occurred in water stress conditions helped avoiding permanent damage to Q. ilex leaves, although during the O3 treatment photosynthesis was severely limited by stomatal closure. In well-watered plants, O3 fumigation caused a noticeable increase of nocturnal stomatal conductance. If confirmed on adult plants under field conditions, this effect can imply larger flux of O3 at night and possible detrimental effects of O3 on leaf functions in plants exposed to high nocturnal O3 levels.

Ecophysiological studies of Mediterranean plant species at the Castelporziano estate (Atmospheric Environment, 1997)
e aim of this work was to characterize the eco-physiological performance of the main plant species of the Castelporziano site by single leaf investigations. We measured the leaf gas exchange of Quercus ilex L., Pinus pinea L., Pistacia lentiscus L. and Asphodelus microcarpus L. for several days. Additionally, the xylem water potential of Quercus ibex, Pinus pinea and Pistacia lentiscus was recorded in order to obtain more physiological background information for the discussion of the trace gas emissions. This study indicates significantly different physiological responses to the different environmental condi- tions. In particular, summer conditions (high values of light, air temperature and low xylem water potentials) caused the depression of photosynthesis in Quercus ibex and Pinus pinea but did not affect photosynthesis of Pistacia lentiscus and Asphodelus microcarpus. This should be taken into account when discussing VOC emission rates and fluxes